Sistem Perekam Detak Jantung Berbasis Internet Of Things (IoT) dengan Menggunakan Pulse Heart Rate Sensor - Adi Hermansyah; Reska Hardiyanti; Aditya Putra Perdana Prasetyo (JTEV (Jurnal Teknik Elektro dan Vokasional), 2022)
Heart rate is a very vital part for the human body, if the heart rate exceeds the maximum limit it will be very dangerous for the body. So we need a heart rate recorder that can store data from the recorded heart rate in order to make it easier to control health. This study aims to test the heart rate recording system with a comparison of a factory-made device, namely an oximeter. This research starts from creating a framework stage that will outline the sequence to be carried out. Heart rate increased after exercise, which was 114.4 bpm compared to 90.8 bpm when eating and relaxing to 66.6 bpm. The results of the data obtained from the test are 60% (3 out of 5 people) who have the same heart rate either using a device or using an oximeter. The average accuracy value of the heart rate recording system when compared to the oximeter is relatively small, namely 1-2 bpm.